2016
DOI: 10.1259/bjr.20150728
|View full text |Cite
|
Sign up to set email alerts
|

Is diffusion tensor imaging useful in the assessment of the sciatic nerve and its pathologies? Our clinical experience

Abstract: Objective: To evaluate the usefulness of diffusion tensor imaging (DTI) in the clinical setting as a complementary tool to conventional MRI in the study and assessment of the sciatic nerve and its pathologies. Methods: 17 patients diagnosed with different types of sciatic neuropathy and 10 healthy controls underwent a conventional MRI and a DTI study in a 3-T MR scanner (Achieva® 3-T X-Series; Philips Healthcare, Netherlands). Results: In the control group, we were able to track and visualize the common sciati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Recently, advanced MRI techniques such as diffusion tensor imaging (DTI) has been studied in the evaluation of sciatica. These studies have found a lower fractional anisotropy (FA) and higher apparent diffusion coefficient values in the affected nerves in comparison with the contralateral side [18,19].…”
Section: Imagingmentioning
confidence: 97%
“…Recently, advanced MRI techniques such as diffusion tensor imaging (DTI) has been studied in the evaluation of sciatica. These studies have found a lower fractional anisotropy (FA) and higher apparent diffusion coefficient values in the affected nerves in comparison with the contralateral side [18,19].…”
Section: Imagingmentioning
confidence: 97%
“…Routine MRI has been widely used to study the normal anatomy and pathology of the sciatic nerve and the associated muscle oedema or denervation, especially on T2-weighted sequences [ 67 ]. DTI may implement conventional MRI examination, providing additional information regarding the myelinic structures [ 68 ]. DTI does not show significant differences in either FA or ADC values at any level between sciatic nerve in the dominant or non-dominant lower limb.…”
Section: Specific Applications In the Musculoskeletal Systemmentioning
confidence: 99%
“…Manoeuvres of flexion, adduction and internal rotation of the hip, and direct palpation of the piriformis, cause severe pain. CT and MRI may help to diagnose PS and to differentiate it from other possible causes of lower lumbar pain; however, imaging diagnosis remains challenging [ 68 ].…”
Section: Specific Applications In the Musculoskeletal Systemmentioning
confidence: 99%
“…The diffusion-weighted data were transferred to a workstation for analysis and eddy current compensation was performed by affine registration to B0 image. Tractography was carried out using the PRIDE fiber-tracking tool (Philips Medical Systems) as described previously (Alfaro et al, 2015 ; Bernabeu et al, 2016 ) and was fulfilled based on the connection between two areas of regions of interest (ROIs), the ROIs were drawn manually based on the anatomical MRI and on published atlases (Wakana et al, 2004 ). The fibers were computed automatically by the software with the following parameters as stopping criteria: minimum fractional anisotropy value (FA) of 0.3, maximum fiber angle between fibers of 27° and minimum fiber length of 10 mm.…”
Section: Case Reportmentioning
confidence: 99%